Digital Storytelling in Moral and Akhlaq Education: A Systematic Review of Strategies and Effectiveness - Kusnindar, Dida Fatra; Prayitno, Teguh; Suprihat, Ade; Qomarudin, Qomarudin; Fatihah, Nur Trisna (International Education Trend Issues, 2025)
This article aims to explore the strategies and effectiveness of digital storytelling (DST) in the context of moral and akhlak education. As the world becomes increasingly digital, educators are integrating technological tools to foster moral development in students. DST is one such tool that holds promise in enhancing the learning of moral values and ethics (akhlak). A systematic review was conducted using library research to analyze the existing literature on the application of DST in moral and akhlaq education. Relevant academic papers, books, and other scholarly articles published between 2015 and 2024 were reviewed. The research focused on examining different strategies for implementing DST and evaluating its effectiveness in promoting moral and ethical education. The review revealed that DST enhances student engagement, critical thinking, empathy, and ethical decision-making. Various strategies, including narrative-based learning, multimedia integration, and interactive storytelling, have proven effective in moral and akhlaq education. Additionally, DST fosters active participation, making learning more engaging and relevant to modern learners. The findings suggest that integrating DST into moral and akhlaq education can significantly improve the teaching and learning of ethical values. Educational institutions should consider adopting DST in their curricula to address the challenges of imparting moral education effectively in the digital age. Further studies are recommended to explore long-term effects and pedagogical frameworks for DST in this domain.